Associations of situational and performance variables with defensive transitions outcomes in FIFA World Cup 2018. Issue 1 (February 2021) - Freitas, Rui; Volossovitch, Anna; Almeida, Carlos H
Transition moments play a major role in match outcome and constitute an important part of the soccer coaching process. Nevertheless, the body of literature on match analysis reveals a lack of knowledge regarding transition moments, particularly the defensive ones. This study aimed to analyse how several situational and performance variables were associated with different defensive transition outcomes. A sample of 977 defensive transitions from 15 matches of FIFA World Cup 2018 was coded using a bespoke observational system. Data were analysed through log-linear modelling and Pearson's chi-square. Regarding performance variables, final position ( p  ≤ 0.001; ES = 0.390[≥0.290]; large effect size), duration ( p  ≤ 0.001; ES = 0.206[0.07; 0.21]), defensive approach ( p  ≤ 0.001; ES = 0.419[0.30; 0.50]), defensive pressure ( p  ≤ 0.001; ES = 0.147[0.05; 0.15]; medium effect sizes), numerical relations ( p  ≤ 0.05; ES = 0.113[0.07; 0.21]), initial position ( p  ≤ 0.05; ES = 0.092[0.06; 0.17]), initial number of zones ( p  ≤ 0.05; ES = 0.083[0.05; 0.15]), final number of zones ( p  ≤ 0.001; ES = 0.112[0.05; 0.15]) and defensive coverage ( p  ≤ 0.001; ES = 0.130[0.05; 0.15]; small effect sizes) were significantly associated with the defensive transitions outcomes. A small-sized and non-significant association ( p  = 0.126; ES = 0.080[0.07; 0.21]) was found for type of ball loss . Concerning the situational variables, a small-sized and significant association between match outcome and defensive transitions outcome was identified ( p  ≤ 0.05; ES = 0.092[0.07; 0.21]). Our findings provide new knowledge on factors that influence team success in defensive transitions. The coaching staff should be aware that the exploitation of areas behind the most retreated player of the midfield sector ought to be avoided. Furthermore, a reduction in the space available to ball carriers and an increased effort to quickly recover possession should be encouraged.